Long-term neurorehabilitation outcomes of pediatric vs. adult onset acquired brain injury - Johnson, Spring Flores; Klonoff, Pamela S.; Perumparaichallai, Ramaswamy Kavitha (Frontiers in Neurology, 2022)
Background Functional outcomes of intensive neurorehabilitation for pediatric onset acquired brain injury (ABI) are understudied. The extent and pervasiveness of impairments are often uncovered years after an ABI and can worsen over time, leading to a cascade of academic, functional, and psychosocial difficulties. Objective To examine the long-term outcomes of survivors with pediatric onset vs. adult onset ABI who completed holistic milieu-oriented neurorehabilitation up to 30 years ago. Methods One hundred twenty-three survivors of ABI including a pediatric onset group (n = 22) and an adult onset group (n = 101) with heterogeneous neurological etiologies who attended holistic, milieu-oriented neurorehabilitation. Productivity, driving, and functional outcomes were evaluated using the Mayo-Portland Adaptability Inventory-4 (MPAI-4) and a psychosocial outcome questionnaire. Treatment for the pediatric onset group started much later than onset. Results A one-way analysis of covariance revealed no significant differences between the two groups on the MPAI-4. At the follow-up survey, there was no significant difference between age at onset of injury and productivity status. The average follow-up time was 8 years (SD = 6.28) from time of discharge to the time of the survey. Although there was no significant difference between the two groups for driving at the time of admission, the adult onset group was significantly more likely to return to driving after treatment. Conclusions This study demonstrates the positive and enduring benefits of holistic, milieu-oriented neurorehabilitation for survivors of pediatric onset ABI regardless of the time between initial injury and engagement in rehabilitative therapies.